Changing the way you teach, improving the way students learn [ - Martin-Kniep, Giselle O. , 1956-; Picone-Zocchia, Joanne (Gale virtual reference library, 2009)
Provides a framework for effective teaching that can be applied in any subject area and grade level and practical tips on how to use rubrics, checklists, and point systems to convey your expectations